Suicide ideation, dementia and mental disorders among a community sample of older people in Mexico. (1st May 2014) - Borges, Guilherme; Acosta, Isaac; Sosa, Ana Luisa
<x xml:space="preserve">Abstract</x> Data on the prevalence of and risk factors for suicide ideation among older people in developing countries is lacking. Objective This study aimed to estimate if dementia and other mental disorders are associated with suicide ideation among the older people controlling for demographic and other suspected risk factors. Methods We report on the Mexican study of dementia, part of the 10/66 international dementia research group, a series of cross‐sectional population‐based surveys in low and middle income countries. A survey was conducted to all residents aged 65 years and older from urban and rural catchment areas in Mexico City and Morelos (January 2006 to June 2007). Results After 18 months of field work, a total of 2003 completed interviews were obtained, with a response rate of 85.1%. We found a lifetime prevalence of suicide ideation of 13.5% and a 2‐week prevalence of 4.2%. The common factors associated with both lifetime and 2‐week prevalence were having a large number of physical disorders (lifetime prevalence ratio = PR and 95% confidence interval = CI; PR = 2.23, CI = 1.63–3.06), depression (PR = 1.92, CI = 1.36–2.70) and anxiety (PR = 2.23, CI = 1.68–2.97) and screening positive for psychosis (PR = 1.64, CI = 1.15–2.34). Conclusion Dementia plays a minor role on suicide ideation after the other aforementioned variables were taken into account and its effect, if any, could be concentrated among those elders with lower severity scores of dementia. These results show the great challenges that Mexico faces in providing services for the older people with suicidality. As the population in the country ages, suicidality will constitute an additional challenge to the healthcare system. Copyright © 2014 John Wiley & Sons, Ltd.